Link : homomaandblad. (Gent : De roze pers, 1980)
Fonds Suzan Daniel (FSD)
Periodiciteit : maandelijks
Redactie : postbus 395, 9000 Gent ; vanaf 02(1982) Walenstraat 4, 2000 Antwerpen
S/95/120
S/91/205
Nederlands
Periodiek